Citrullination of proteins: a common post-translational modification pathway induced by different nanoparticles in vitro and in vivo. (August 2012) - Mohamed, Bashir M; Verma, Navin K; Davies, Anthony M; McGowan, Aoife; Crosbie-Staunton, Kieran; Prina-Mello, Adriele; Kelleher, Dermot; Botting, Catherine H; Causey, Corey P; Thompson, Paul R; Pruijn, Ger JM; Kisin, Elena R; et al.
Aim: Rapidly expanding manufacture and use of nanomaterials emphasize the requirements for thorough assessment of health outcomes associated with novel applications. Post-translational protein modifications catalyzed by Ca 2+ -dependent peptidylargininedeiminases have been shown to trigger immune responses including autoantibody generation, a hallmark of immune complexes deposition in rheumatoid arthritis. Therefore, the aim of the study was to assess if nanoparticles are able to promote protein citrullination.Materials & methods: Human A549 and THP-1 cells were exposed to silicon dioxide, carbon black or single-walled carbon nanotubes. C57BL/6 mice were exposed to respirable single-walled carbon nanotubes. Protein citrullination, peptidylargininedeiminases activity and target proteins were evaluated.Results: The studied nanoparticles induced protein citrullination both in cultured human cells and mouse lung tissues. Citrullination occurred via the peptidylargininedeiminase-dependent mechanism. Cytokeratines 7, 8, 18 and plectins were identified as intracellular citrullination targets.Conclusion: Nanoparticle exposure facilitated post-translational citrullination of proteins. Original submitted 18 March 2011; Revised submitted 10 November 2011; Published online 25 May 2012